2017
DOI: 10.1139/cjfas-2016-0298
|View full text |Cite
|
Sign up to set email alerts
|

Downstream migration and mechanisms of dispersal of young fish in rivers

Abstract: Downstream migration (DSM) of young fish has traditionally been considered a passive process. A review of studies of the patterns and mechanisms of DSM showed that it met the main criterion for migration: that animals move between well-defined habitats according to a predictable schedule. During DSM, fish often leave the habitat in which they reside (inshore zone) and enter a migratory habitat (main channel). DSM is manifested at a seasonal or diel scale and in species-specific spatial distribution patterns. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…As stated by Pavlov and Mikheev [54], during dispersal, the local densities of migrating fish may become low. This could hinder essential interactions as group formation.…”
Section: Introductionmentioning
confidence: 92%
“…As stated by Pavlov and Mikheev [54], during dispersal, the local densities of migrating fish may become low. This could hinder essential interactions as group formation.…”
Section: Introductionmentioning
confidence: 92%
“…Several salmonids perform downstream migration at night (Hintz & Lonzarich, 2012; Johnston, 1997; Pavlov & Mikheev, 2017). In general, except for some large rivers, high turbidity conditions and polar‐day conditions, the fry of the pink salmon Oncorhynchus gorbuscha perform downstream migration at night (Ali & Hoar, 1959) and finish their migration overnight (Heard, 1991); however, since the previous studies about diel migration of pink salmon have been conducted in rivers of various sizes ( e.g ., Kirillov et al ., 2018; Neave, 1955; Pavlov et al ., 2015), these studies have shown different results between rivers or surveys.…”
Section: Metric Chienbetsu Stream Funbe Stream Syoji Streammentioning
confidence: 99%
“…Therefore, our study shows that individuals emerging in small streams quickly migrated to the sea. Other salmonids show nocturnal downstream migration: the brown trout Salmo trutta , coho salmon O. kisutch , Atlantic salmon S. salar and rainbow trout O. mykiss (Hintz & Lonzarich, 2012; Johnston, 1997; Pavlov & Mikheev, 2017). Nocturnal migration may be a strategy to avoid predation (Ibbotson et al ., 2011; Johnston, 1997; Kennedy et al ., 2018).…”
Section: Metric Chienbetsu Stream Funbe Stream Syoji Streammentioning
confidence: 99%
“…A key aspect of improving control and monitoring of grass carp larvae in streams relies on understanding their behaviour from hatching until the development of their swimming capabilities. While there are several biotic factors that might affect larval drift (e.g., Lechner et al 2016;Pavlov and Mikheev 2017, and references therein), our study focuses on the larval response to hydrodynamic features. Larval response to flow conditions is dependent on the species and their developmental stage (Pavlov et al 2008;Lechner et al 2014).…”
Section: Introductionmentioning
confidence: 99%